A Qualitative Analysis of WHO’s International Standard Terminologies on TCM - Han LAI; Aaron Lee Moore; Xiaodan YAN; Weihong LI; Yang YANG (Chinese Medicine and Culture)
Abstract. Traditional Chinese medicine (TCM) is increasingly recognized worldwide as a valuable complementary and alternative medicine. To facilitate global research and collaboration in this field, the World Health Organization (WHO) introduced the International Standard Terminologies on Traditional Chinese Medicine in 2022. This international terminology translation standard, IST 2022, goes beyond conventional translation by embracing three innovative features: 1) It reflects TCM’s foundational philosophy of unity and opposition, emphasizing the interconnectedness among TCM terms during translation. This approach transcends individual term translations to explore the interrelationships among them. 2) It preserves the integrity of TCM theory by retaining transliterations for unique TCM terms that possess distinct features. 3) It employs innovative xiang (image) cognition, a concept rooted in traditional Chinese thought by helping readers grasp visual and mental imagery associated with each term. This study presents a qualitative analysis based on interviews with 11 TCM translation experts, examining their perspectives on these features and their translational preferences across the IST 2007 and 2022 versions. These findings contribute to the standardization and global harmonization of TCM terminology, advocating for clarity, precision, and the advancement of TCM in the international healthcare arena.